Health Beliefs about Cervical Cancer and Cervical Cancer Screening among Women at Shai Osudoku District - Appiah, E.O. (University of Ghana, 2019)
Cervical cancer is one of the leading causes of death among women in Ghana and the world at large. Cervical cancer screening has been proven to be effective in reducing the incidence, morbidity and mortality associated with cervical cancer worldwide. It helps to detect cervical cancer at precancer stage before cancer develops. Despite this, it is not always available in most low- and middle-income countries as compared to high income countries. In countries where it is available it is either expensive, or not covered by the NHIS coupled with other barriers that prevent women from engaging in the screening services. Patronage in cervical cancer screening is low in middle and low income as compared to high income countries due to some barriers including health beliefs of women. The study therefore explored the health beliefs about cervical cancer screening among women at Shai Osudoku District in the Greater Accra Region. Qualitative exploratory descriptive method was employed using purposive sampling technique to select participants. Seventeen (17) women were purposively sampled and engaged in an interview using a semi structured interview guide which lasted for 30-45 minutes. All interviews conducted were audio taped, transcribed verbatim and analysed using thematic analysis. Six major themes emerged based on the constructs of the HBM and two other themes emerged in relation responses of participants. In all, 31 subthemes were formulated. Findings of this study revealed several views women have about CC/CCS including meaning of CC/CCS, severity of CC, women susceptibility to CC, CCS benefits, CCS barriers, cues to CCS, reaction towards CC diagnosis and strategies to overcome CCS. Findings suggest that generally women have inadequate knowledge about CC/CCS leading to low patronage in CCS. Findings of this study have implications for nursing practice and nursing research policy regarding CCS cost, treatment and HPV vaccination, to help increase Utilization of CCS services.
MPhil. Nursing
Keywords: Health Belief Model; Cervical Cancer; Shai Osudoku District